PENGGUNAAN MEDIA PEMBELAJARAN KARTU HURUF DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SD KARTIKA XIII-1 AMBON - Nurhiyani Rukua; Sarah Sahetapy; Ribka L. Ririhena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of using letter cards as learning media in improving the early reading skills of second-grade students at Kartika XIII-1 Ambon Elementary School. The research method used was classroom action research with two cycles, each applying four stages, namely planning, implementation, observation, and reflection. The results of the study show that the use of letter cards as a learning aid is very effective in improving the early reading skills of second grade students at Kartika XIII-1 Ambon Elementary School. This improvement is demonstrated through more active student participation and learning outcomes that show significant progress in letter recognition, syllables, and word combinations.